“Enhancement of Nitrogen Removal in the Compact Extended Aeration Reactor (CEAR) by using Attached Growth System” - Mohd Som, Siti Nazira (Universiti Teknologi PETRONAS, 2013)
As the Nitrogen limit in water body becomes more stringent, the treatment system also needs to be upgraded. Plus, due to human population that kept increasing by days, the area for the system was limited. Adopting the CEAR (Compacted Extended Aeration System) as the system to be used, this system will be modified to increase the efficiency in removing Nitrogen. CEAR is an integrated reactor that use activated sludge system for the wastewater treatment, where it consist of aeration, anoxic and clarifier compartments. Previously it has been tested and produced significant effluent of Ammonia and Nitrate of 0.5 mg/L and 0.3 mg/L respectively (Sani F. A., 2012). The modification done in this project was the insertion of attached growth media in both aeration and anoxic compartments after the role of the compartments in the reactor had been changed. The Aero-packer was installed in the aeration compartment, while the Bio-balls were inserted into the anoxic compartment. Experimental works were done to justify the effects of the installation of the attached growth media in the CEAR. For that, the wastewaters from the aeration tank of UTP STP together with the formulated synthetic wastewater were used as experimental materials. The reactor was operated in two phases, first for 35 days with 10 L/d and 15 L/d of influent flowrate to monitor the performance of CEAR without the attached growth media. Continuing that, the reactor was run for another 18 days with the attached growth media by using 15 L/d flowrate in the second phase. From the experiment done, the average final effluent during the first phase gave an average effluent 17.4 mg/L of Ammonia concentration and 0.4 mg/L Nitrate concentration. These provide an overall percentage removal of 34.3% and 80.9% for Ammonia and Nitrate respectively. During the second phase, the average final effluent gave 18.6 mg/L and 1.1 mg/L of Ammonia and Nitrate concentration respectively. These provide 24.8% and 47.6% of overall removal rate respectively. Therefore, the objective of the attached growth media to enhance the Nitrogen removal was not achieved because the percentage of removal is higher in the first phase. However, the conclusion was made irrespective to the control towards alkalinity and Carbon source since they cannot be determined due to technical problems. Thus, the recommendation proposed was to make further study on how to accurately add the additional alkalinity and Carbon source so that the performance of the CEAR can be optimized.